Twice a day lacrosse training in temperate conditions results in a negative 24-hour sodium balance in male and female university lacrosse players - Macrae, H. Z.; Reynolds, K. M.; Cable, T. G.; Barutcu, A.; Hansell, E. J.; Mears, S. A.; Midwood, K. L.; Mould, C.; Funnell, M. P.; Goosey-Tolfrey, V. L.; James, L. J. (The Journal of Strength and Conditioning Research, 2025)
This study measured 24-hour fluid and sodium balance in 27 university lacrosse players (13 males, 14 females; 21 ± 1 years). For 24 hours, participants maintained their usual fluid and food intake, completed a weighed food diary, and collected all urine produced. Participants completed 2 bouts of 1.5 hours (males) or 2 hours (females) lacrosse training (16.0 ± 3.9°C, 62.3 ± 11.7% relative humidity) separated by 2-2.5 hours rest. Nude body mass was measured at baseline (0 hour), 24 hours later, before and after training, and corrected for food/fluid consumed and urine/feces produced during training to determine sweat losses. A sweat patch was applied (scapula) and analyzed for sweat sodium concentration. Data are mean ± standard deviation or median (Q1-Q3), p < 0.05. Sodium balance at 24 hours was negative for both male (-0.76 ± 1.31 g) and female (-0.47 ± 0.70 g) players but was not different between sexes (p = 0.350). Body mass at 0 hour and 24 hours was not different for male (79.99 ± 10.02 kg vs 79.69 ± 10.15 kg) or female (65.68 ± 10.17 kg vs 65.82 ± 10.21 kg; both p > 0.05) players. Sweat rates were relatively low and not different between male (0.39 ± 0.23 L/h) and female (0.33 ± 0.18 L/h; p = 0.286) players. There was no difference in sweat sodium concentration (male players: 27 (23-28) mmol/L; female players: 27 (23-31) mmol/L; p = 0.786). Ad libitum drinking, combined with low sweat rates, generally prevented dehydration accruing to a level that might impair performance. Sodium balance deficit was small (~0.61 g) but may require investigation to understand whether daily deficits accumulate.